School-based delivery of routinely recommended vaccines and opportunities to check vaccination status at school, a global summary, 2008–2017. Issue 3 (16th January 2020) - Feldstein, Leora R.; Fox, Garrett; Shefer, Abigail; Conklin, Laura M.; Ward, Kirsten
Highlights: From 2008 to 2017, % countries with school-based vaccination (SBV) increased (58%−60%). 28 countries reporting no SBV (or no response) in 2008 reported SBV in 2017. In 2017, 108 of 181 countries reported using SBV, delivering 18 different antigens. High (>80%) home-based record availability and primary school enrollment in countries with SBV. 33 countries have high potential to implement checking of vaccination status at school. Abstract: School-based vaccination (SBV) and checking students' vaccination records at school have the potential to optimize vaccination coverage among school-aged children. The primary aim of this paper is to describe adoption of SBV by countries from 2008 to 2017, including target age groups and vaccines delivered in 2017, as reported annually through the World Health Organization (WHO)-United Nations Children's fund (UNICEF) Joint Reporting Form (JRF). Expanding upon previous analyses, country-specific rates of primary school enrollment and home-based record (HBR) ownership were linked to the WHO-UNICEF JRF data, to identify countries with high potential to implement vaccination record checks at school. The proportion of countries reporting delivery of at least one routinely recommended vaccine dose in school settings increased from 95 (of 163 reporting; 58%) in 2008 to 108 (of 181 reporting; 60%) in 2017. The 13 additional countries that reported using SBV in 2017 were among 31 countries for which SBV data from the JRF were unavailable in 2017. The most common antigens delivered through SBV in 2017 were tetanus (94 countries), diphtheria (89 countries), and human papillomavirus (52 countries). Among 93 countries with data available for net primary school enrollment and HBR ownership, 52 (56%) countries had both ≥80% net primary school enrollment and ≥80% of children aged 12–23 months ever owning an HBR; 33 (63%) of these used SBV. If not already doing so, these 33 countries represent an opportunity to introduce routine checking of vaccination status at entry to, or during primary school. With the growing number of new vaccines and booster doses of childhood vaccines targeting school-age children, implementation of SBV and checking of student vaccination records at school may help improve vaccination coverage; however, additional data are needed to assess global prevalence of checking vaccination status at school and to identify factors facilitating optimal implementation of this strategy.